Analisis Pengaruh Ukuran Perusahaan, Kebijakan Deviden, Keputusan Investasi, Profitabilitas Terhadap Nilai Perusahaan (Studi Index LQ 45 periode 2012-2015) - Putri Anggita Sari, Sella, Drs,Farid Wajdi, M.M, Ph.D (2017)
This study aimed to measure the influence of firm size, dividend policy, investment decision and profitability on the firm value. Firm value was an indicator of financial performance in a go public company. A high firm value indicates stakeholders prosperity. This study was conducted on JII company that were listed in the Indonesia Stock Exchange for the period 2012-2015.This study involved 40 companies for the samples, during the period 2012-2015. This study used purposive sampling to determine the samples, with multiple linear regressions. The analysis concluded that firm size had no influence on the firm value, in line with the dividend policy. The profitability gave influence to the firm value, as well as investment decision.